2020
DOI: 10.1002/jcc.26473
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of long‐range corrected density functional theory on the absorption and vibrationally resolved fluorescence spectrum of carbon nanobelts

Abstract: Time-dependent (TD) density functional theory (DFT) and Franck-Condon Hertzberg-Teller (FCHT) calculations of various DFT functionals [B3LYP, CAM-B3LYP, ωB97XD, and optimally tuned (OT) long-range corrected (LC)-BLYP] were performed to examine how well DFT functionals can predict the experimental absorption and fluorescence spectra of a 12-carbon nanobelt (CNB). OT-LC-BLYP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Accordingly, most of the excited states generated by UV light absorption are primarily relaxed through the S 0 ← S 1 transition; in other words, a minority of the excited states are relaxed with relatively high yield through the symmetry-allowed S 0 ← S 2 transition and hence appear as the detectable excitation spectrum at 495 nm, corresponding to the zero-Stokes shift emission. Notably, some uncertainty remains in the transition assignment …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, most of the excited states generated by UV light absorption are primarily relaxed through the S 0 ← S 1 transition; in other words, a minority of the excited states are relaxed with relatively high yield through the symmetry-allowed S 0 ← S 2 transition and hence appear as the detectable excitation spectrum at 495 nm, corresponding to the zero-Stokes shift emission. Notably, some uncertainty remains in the transition assignment …”
Section: Resultsmentioning
confidence: 99%
“…The symmetry-forbidden S 0 → S 1 transition corresponds to HOMO → LUMO, and the symmetry-allowed S 0 → S 2 transition corresponds to HOMO–1 → LUMO/HOMO → LUMO+1. However, there is still an element of uncertainty in the assignment …”
Section: Resultsmentioning
confidence: 99%
“…Even though a bound dimer was prevalent, the absence of π–π stacked geometry at B3LYP and X3LYP levels (Table S1 and Figure S3, SI) revealed the hybrid functionals to be nonresponsive toward π–π stacking . Hybrid functionals such as B3LYP and X3LYP are flawed by errors on account of inadequacies in assessing long-range dispersion interactions, while M05-2X, M06-2X, and ωB97X-D account well for the dynamic dispersion interactions including long-range-corrected electron correlation effects and electrostatics (H-bond). Among all of the hybrid meta and the DFT functionals employed to describe NFP–pybate, ωB97X-D yielded the best performance in estimating the interaction energies and hence NFP–2-pybate, NFP–4-pybate, and NFP–3-pyba were computed at this level. The minima for NFP–2-pybate, NFP–4-pybate, and NFP–3-pyba at the ωB97X-D level were obtained at π–π distances of 3.07, 3.06, and 3.22 Å with binding energies of −37.49, −44.93, and −19.66 kcal/mol, respectively (cf.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, CNBs are supposed to have remarkable charge transport properties 15 and be generally more conductive than linear conjugated semiconductors, 5 which was confirmed by both experimental 14 and computational studies. 34 Lastly, photophysical measurements 13,30 and excited-state simulations 35,36 demonstrated that CNBs exhibit peculiar photophysical and fluorescent properties, and as envisioned in ref 35, we could make use of the supramolecular chemistry of CNBs to modulate these properties by varying the guest species.…”
Section: Introductionmentioning
confidence: 88%